Construction of an ‘acne reduction clock’ and treatment success with combination of Ocimum basilicum & Aloe vera - G.V, Amruthavalli; V, Aruna; R, Gayathri (Journal of Medicinal Herbs and Ethnomedicine, 2019)
Acne/pimple is a chronic skin condition with hair follicles blocked with sebum/dirt/dead cells. This leads to inflammation and also increases the microbial load. Acne occurs due to various reasons such as seasons, enzymes, environmental conditions, microbial load, excess sebum deposition etc. There are various conventional treatments available but are not satisfactory or may have some side effects. Herbal drugs play a major role in the treatment of acne. The combination of Ocimum basilicum & Aloe vera is proven to have anti-microbial and anti-inflammatory activities. In the present paper herbal product with combination of Ocimum basilicum & Aloe vera was studied for its efficacy on hourly basis. Results are presented in the paper.